A Case of Peritoneal Encapsulation Presented as Acute Mechanical Small Bowel Obstruction: A Case Report and a Brief Literature Review. (11th August 2022) - Abuzaina, Khalil; Abuayash, Ahmad; Al-Shweiki, Hidaya; Hroub, Mohammad O. M.; Jabari, Anwar Yousef; Hafiz, Shayma; Ihlayel, Tuqa Abu; Mohsen, Balqees; Fakhouri, Sulaiman Naji; Jaa'freh, Murad
Abstract : Peritoneal encapsulation (PE) is a rare congenital malformation in which the small intestine is partially or totally encased in a supplementary peritoneal sac. PE is usually asymptomatic; therefore, it is one of the rarest etiologies of bowel obstruction. Our patient presented at the age of 55 with no prior surgical history and a 3-day history of abdominal pain associated with nausea, vomiting, belching, and constipation. An obstruction secondary to an internal hernia—visualized on a CT scan—was suspected as the initial etiology. On exploratory laparotomy, the small bowel was covered by a thick adherent sac. These findings are consistent with PE, a condition that deserves recognition among clinicians worldwide. Intraoperatively, the sac was excised, and the small bowel was pulled up to the peritoneal cavity starting from the ileocecal valve to the duodenojejunal junction. In the postoperative period, the patient was managed with intravenous fluids, analgesics, and antibiotics. Wound infection was the only postoperative complication. Otherwise, all symptoms subsided, and the patient improved and was discharged home on the 8th postoperative day.